TEACHERS' DIFFICULTIES IN TEACHING WRITING DESCRIPTIVE TEXTS - Annisa, Hasni (2013)
This study was conducted to investigate the teachers' difficulties in teaching writing descriptive texts to the 10th grade students and their strategies to overcome the difficulties. The participants of the study were two English teachers at a senior high school in Pangkal Pinang. This was a descriptive case study using qualitative method as the approach. The data in this study was collected using two techniques: classroom observation and interview. This study yielded two results. In teaching writing descriptive texts, the teachers faced eight difficulties. Those difficulties were related to the students, to the teachers, to the writing itself, and to the school's policy. It was also found that the teachers used six strategies to overcome those difficulties, including one-to-one guidance during the learning process, motivating students through encouraging stories, maximizing the utilization of students' workbook, continuing to learn outside of school (through various media), sharing their teaching experiences with other teachers, and joining training and development programs. Key words: difficulties in teaching, writing, descriptive text, strategies